Anthropogenic Release and Distribution of Titanium Dioxide Particles in a River Downstream of a Nanomaterial Manufacturer Industrial Site - Slomberg, Danielle L.; Auffan, Mélanie; Guéniche, Nelly; Angeletti, Bernard; Campos, Andrea; Borschneck, Daniel; Aguerre-Chariol, Olivier; Rose, Jérôme (Frontiers in Environmental Science, 2020)
Several industries manufacture and process large quantities of engineered nanomaterials, thus increasing the potential for their environmental release during waste management and disposal. Herein, we quantified the release and spatial distribution of titanium dioxide nanomaterials (TiO2 NMs) emitted from an industrial waste stream that flows into a nearby river. Two sampling campaigns were carried out on the river in fall 2017 and spring 2018 at selected sites upstream and downstream of the Industrial Effluent and an urban wastewater treatment plant (WWTP). Significant Ti accumulation was detected in the sediments at the Industrial Effluent and WWTP sites for both fall and spring samples, with measured Ti concentrations of 75−193 mg Ti/kg reaching 21−55× that of the local background upstream. X-ray diffraction analysis confirmed the anatase and rutile mineralogy of the inputs. River surface waters were filtered on-site to distinguish between particulate (>0.20 μm), colloidal (0.02−0.20 μm), and dissolved and/or small nanoparticulate (NP) (< 0.02 μm) TiO2. Up to 133 and 260 μg Ti/L were measured in the unfiltered waters for the Industrial Effluent and WWTP fall samples, respectively, while the spring samples exhibited Ti concentrations similar to the background concentration. Combining chemical analysis and scanning electron microscopy revealed that some Ti particles recovered from the Industrial Effluent and WWTP were clusters of TiO2 NMs (~50 nm). Furthermore, anthropogenic TiO2 was distinguished apart from natural Ti-containing minerals by comparing the concentration ratios between Ti and other naturally occurring elements (e.g., V, Al, and Fe). This study confirmed the release of manufactured TiO2 NMs from the Industrial Effluent and the WWTP into the river, finding that almost all of the TiO2 NMs are released in the particulate fraction (>0.20 µm), and that the particles sediment rapidly near the emission source and accumulate in the sediment.